Analysis of genomic responses in a rat lung model treated with a humidifier sterilizer containing polyhexamethyleneguanidine phosphate. (15th February 2017) - Kim, Min-Seok; Jeong, Seok Won; Choi, Seong-Jin; Han, Jin-Young; Kim, Sung-Hwan; Yoon, Seokjoo; Oh, Jung-Hwa; Lee, Kyuhong
Highlights: We investigated the geno-toxicological effects of PHMG phosphate in the rat lung using a DNA microarray. PHMG phosphate altered expression of genes involved in the urea cycle, inflammation, and oxidative stress. 21 genes were induced and 4 genes were repressed in response to PHMG phosphate in a timedependent manner. Abstract: The antimicrobial biocide polyhexamethyleneguanidine (PHMG) phosphate is the main ingredient in the commercially available humidifier disinfectant. PHMG phosphate-based humidifier disinfectants can cause pulmonary fibrosis and induce inflammatory and fibrotic responses both in vivo and in vitro . However, toxicological mechanisms including genomic alterations induced by inhalation exposure to PHMG phosphate have not been elucidated. Therefore, this study evaluated the toxicological effects of the PHMG phosphate-containing humidifier disinfectant. We used DNA microarray to identify global gene expression changes in rats treated with PHMG phosphate-containing humidifier disinfectant for 4 weeks and 10 weeks. Functional significance of differentially expressed genes (DEGs) was estimated by gene ontology (GO) analysis. Four weeks post-exposure, 320 and 392 DEGs were identified in female and male rats, respectively (>2-fold, p  < 0.05). Ten weeks post-exposure, 1290 and 995 DEGs were identified in females and males, respectively. Of these, 119 and 556 genes overlapped between females and males at 4 weeks and 10 weeks, respectively, post-PHMG phosphate exposure. In addition, 21 genes were upregulated and 4 genes were downregulated in response to PHMG phosphate in a time-dependent manner. Thus, we predict that changes in genomic responses could be a significant molecular mechanism underlying PHMG phosphate toxicity. Further studies are required to determine the detailed mechanism of PHMG phosphate-induced pulmonary toxicity.